INSTITUCIONALIDAD DE LOS BIENES PÚBLICOS: APROXIMACIÓN A LAS EXPERIENCIAS DEL PERÚ, CHILE Y COLOMBIA - Estepa Rodríguez, Lida Fernanda (Revista de Derecho, 2020)
This research examines the institutional experience regarding the public goods of Peru, Chile and Colombia from its legal and doctrinal development. The existence of an institutional deficit in the management of public goods in Colombian law is verified from the experience of countries with similar legal systems. From the state of art, a proposal of institutional of public goods for the country is generated.
Keywords: public goods; institutionality; Peru; Chile; Colombia